ENHANCING CROP PRODUCTIVITY THROUGH WHEAT (T RITICUM AESTIVUM L.) - FENUGREEK INTERCROPPING SYSTEM - A. Wasaya; R. Ahmad; F. U. Hassan; M. Ansar; A. Manaf; A. Sher (Journal of Animal and Plant Sciences, 2013)
Intercropping of wheat and fenugreek may be a viable alternative to sole cropping to increase farmer’s net income and provide understanding of crop performance and productive systems. A field study was conducted to quantify the “agro- economic assessment of wheat (Triticum aestivum L.) fenugreek intercropping system” at Agronomic Research Area, University of Agriculture, Faisalabad during winter 2005 and 2006. The experiment was laid out in a randomized complete block design (RCBD) and comprised of seven treatments viz. wheat alone 30 cm spaced single row, wheat alone 75 cm spaced 4 row strips, wheat +one row of fenugreek, wheat +2 rows of fenugreek, wheat +3 rows of fenugreek, wheat +4 rows of fenugreek and fenugreek alone. Although all the intercrops reduced number of tillers m-2 , number of grains per spike, weight of grains per spike, 1000-grain weight and grain yield of wheat significantly compared to its monocropping, nonetheless, the additional yield obtained from each intercrop compensated more than the losses in wheat production. The land equivalent ratio (LER) showed 19 to 38% yield advantage of intercropping system than sole cropping. The highest yield advantage (38%) was recorded in wheat+3 rows of fenugreek followed by wheat +4 rows of fenugreek (33 %) against the minimum of 19% in wheat +1 row of fenugreek. All the intercropping systems gave substantially higher net income ha-1 over pure stand of wheat. The maximum net income of Rs. 33647 ha-1 was obtained from wheat +3 rows of fenugreek against the minimum of Rs. 24791 ha-1 from sole cropping. It may be concluded that wheat +3 rows of fenugreek is the best intercropping system and can be practiced on large scale by farmers.
Keywords: Intercropping; land equivalent ratio; wheat; grain yield; Economic analysis